Produção da videira Niagara Rosada submetida a indutores de brotação, no Oeste do Paraná - Werle, Tatiana (2011)
In an attempt to induce the grapevines buds sprouting in mild winter regions, characterized by mild temperatures during the hibernal season, it becomes necessary the use of sprouting inducers. Considering the grapevines cultivation expansion in Western Paraná, the current study had as its aims to determine the optimal concentration of hydrogenated cyanamide, ethephon and Stimulate® bio-stimulant for the induction and uniformity of sprouting in Niagara Rosada cultivar, as well to indicate the most effective product in the uniformity sprouting inducing and which promotes improved productivity and fruits quality. The experiment was conducted in a commercial vineyard located in the municipality of Quatro Pontes, West of Paraná State. The experiment was carried out in outlined blocks in factorial scheme 3 X 5, totaling 15 treatments with four repetitions, and each plant was considered an experimental unit. The treatments consisted of the following concentrations: 0; 10 mL L-1; 20 mL L-1; 30 mL L-1 and 40 mL L-1 of hydrogenated cyanamide (H2CN2); 0 ; 2 L ha-1; 4 L ha-1; 6 L ha-1 and 8 L ha-1 of ethephon; 0; 5 mL L-1; 10 mL L-1; 15 mL L-1 and 20 mL L-1 Stimulate® bio-stimulant. The products application was made immediately after pruning, by spraying with backpack sprayer. After pruning, it was assessed the number of buds per plant, time to sprouting onset after application, number and percentage of sprouting per plant, production per plant, expected productivity, average weight of berries, number of berries per cluster, width of shoulder and berries, berries length, soluble solids content, titration total acidity, pH and ratio. Considering the conditions under which the experiment was conducted, one can conclude that: The concentration of hydrogenated cyanamide which showed higher percentage of 'Niagara Rosada' grapevine sprouted buds was the 20mL L-1; the ethephon concentration which provided the highest percentage of Niagara Rosada grapevine sprouted buds was the 8 L ha-1; the bio-stimulant concentration which provided the highest percentage of Niagara Rosada grapevine sprouted buds was the 5 mL L-1; the hydrogenated cyanamide provided the anticipation and uniformity of the Niagara Rosada grapevine sprouting. The buds spraying with hydrogenated cyanamide, ethephon and bio-stimulant resulted in no effect on the grapevine productivity and quality, cv. Niagara Rosada